José Carlos Becerra: the poet at the wheel of eternity - Cerino Córdova, Kristian Antonio (2023)
This article reconstructs the misfortune suffered by José Carlos Becerra, a Mexican poet, who died at the age of 34 in Brindisi, Italy. More than half a century after the event, his poetry is in good health because of the reprint of his poems and because more and more young people have joined who read with amazement the verses of the writer born in Tabasco, southern land of poets. In his youth, Becerra found recognition for his work, like the praise he received -through a letter- from the poet Octavio Paz; however, his scriptural process stopped when he lost his life in that car accident, a fact that shocked the academic community, cultural and literary of Mexico in 1970. Although José Carlos Becerra knew what to do with words, he was not skilled with the steering wheel, according to testimonies of friends and close to the poet who was looking, on the day of misfortune, for a sea trip to Greece.